Project Based Learning untuk Meningkatkan Kemampuan Imajinasi Siswa dalam Pembelajaran Sejarah - Nurbaety Agustina Dewi Ratnasari; Murdiyah Winarti (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2020)
This research is motivated by the lack of students’ ability to express their opinions in detail. These indications seen from information processing only using single source and there is no further processing of resources, thus students less understanding of what they presenting. Some of the problems taken in this study, including: first, how to plan project-based learning, second, how to implement project-based learning, and third, how to reflect on the implementation of project-based learning. This study aims to improve students’ imagination ability in history learning. The research method used is a classroom action research method from Dave Ebbut, beginning with general ideas, reconnaissance (action before action), action plan, action 1, reconnaissance (monitoring after action), choice (changes or not), and next cycles. Aspects from the ability of students’ imagination are high curiosity, identifying facts from relevant sources, being able to express original ideas, being able to produce works, and explaining their work with confidence. The project developed was mind map, writing historical song lyrics, scrapbook, and news anchor presentations. The score of each indicator shows a significant increase in each cycle. This shows the success of implementing Project-Based Learning to improve students’ imagination abilities. Then the results of this study can be used as alternative recommendations for teachers, so students have good imagination ability and learn history more meaningful.